A Convenience Sample Looking at Microbiome Differences Between Anxious and Non-Anxious Patients in a GI Clinic - Sabine Hazan; Mathilda von Guttenberg; Adriana C. Vidal; Norman M. Spivak; Alexander Bystritsky (Gastroenterology Insights)
Background: The gut–brain axis, significantly influenced by the gut microbiome, is a growing focus in mental health research. This study aimed to investigate gut microbiome differences between anxious and non-anxious participants. Methods: A convenience sample of 119 participants consisted of 56 participants with self-assessed low to zero levels of anxiety and 63 with self-assessed mild to severe levels of anxiety, using the self-rated Generalized Anxiety Disorder 7-item (GAD-7) test. Fresh stool samples were collected for bacterial DNA extraction. DNA library preparation was performed using shotgun methodology, sequenced with the NextSeq 500/550 High Output v2.5 300 cycle kit, and mapped using minimap2. Bioinformatics analysis was conducted using One Codex. Results: The study participants were all of white race/ethnicity and the mean age, 54 (anxious group) vs. 55 (non-anxious) yr old, was not different between groups (p = 0.75). In the anxious group, 33% were females versus 25% in the non-anxious group, p = 0.46. Six percent of the anxious group reported a prior diagnosis of depression and 8% had irritable bowel syndrome, compared to none in the non-anxious group (p = 0.02, p = 0.006, respectively). Mann–Whitney tests revealed higher relative abundances of the genera Clostridioides (p = 0.011) and Bacteroides (p = 0.002) in the anxious group. Conversely, the anxious group had lower levels of the genera Bifidobacterium (p = 2.118 × 10−10), Faecalibacterium (p = 0.020), and the Phylum Actinobacteria (p = 1.516 × 10−8). Conclusions: Our findings corroborate previous studies, showing significant gut microbiome differences between anxious individuals and their non-anxious counterparts. These results support further exploration of microbiome-centric anxiety research.